Practical manual on geographical indications for ACP countries - Ngo Bagal, M.; Vittori, M. (CTA / Origin, 2011)
Geographical indications (GIs), which link the quality/reputation of a product to a given location, can contribute to enhancing the value of local products. This manual assists producers and policy-makers who are interested in acquiring the basic knowledge needed to embark on the ‘GI adventure’. Intended to be understood by non-specialists, the text explores the key issues concerning GIs, placing specific emphasis on the interests and needs of ACP countries. For those who want to find out more, references are provided to more specialised and detailed publications.